Carbon fiber composite barium titanate conductive ceramic material as well as preparation method and application thereof
By introducing carbon fiber into piezoelectric ceramics, carbon fiber composite barium titanate conductive ceramic materials are prepared, which solves the problem that traditional connection methods are not suitable for high temperature and high strength occasions, and the reliable connection between barium titanate ceramics and metals is achieved, and the resistivity of the ceramics is reduced.
Patent Information
- Application Number
- CN202510387099.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
AI Technical Summary
It is difficult for the prior art to achieve reliable connection between piezoelectric ceramics and metals. The traditional connection method has problems such as high stress, difficulty in automation of operation, limited scope of application, and inapplicable in high temperature and high strength occasions.
Carbon fiber composite barium titanate conductive ceramic material is prepared by mixing ball milling, drying, granulation molding, glue removal and sintering, and carbon fiber is introduced into BaTiO3 ceramic as a conductive reinforcement to reduce the resistance of the ceramic.
It effectively reduces the resistivity of barium titanate piezoelectric ceramics, provides an intermediate transition layer between barium titanate and metal connection, and provides a new idea for barium titanate piezoelectric ceramics to metal connection, and is suitable for high temperature and high strength occasions.
Smart Images

Figure CN120157472A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of piezoelectric ceramic materials, and particularly relates to a carbon fiber composite barium titanate conductive ceramic material, a preparation method thereof, and an application thereof. Background Art
[0002] Dielectric materials refer to materials that can be polarized under the action of an external electric field but do not conduct electricity themselves. They can store electrical energy and affect the distribution of the electric field. Dielectric capacitors have a high power density and charge-discharge rate, so they are widely used in various electronic devices and pulse devices. Piezoelectric ceramics are one of the commonly used dielectric materials, with the characteristics of corrosion resistance, high temperature resistance, and excellent mechanical properties.
[0003] Under the action of an external stress, the internal atomic structure of piezoelectric ceramics changes, the atomic positions shift, the internal positive and negative charges are unevenly distributed, and charges are generated on the surface to form a voltage. When the piezoelectric ceramic is connected to a circuit system, the generated voltage signal can be captured and amplified by the circuit system, so that the mechanical signal is converted into an electrical signal. This electrical signal can be used to monitor the state of the piezoelectric ceramic after amplification and processing. However, how to efficiently connect the piezoelectric ceramic to the circuit system has become a problem. Due to the differences in physical and chemical properties between ceramics and metals, traditional connection techniques such as welding cannot achieve reliable connection. The current mainstream connection methods are mainly mechanical connection, organic adhesion, and brazing, etc. Mechanical connection refers to a technology that realizes the connection of metal ceramics by using mechanical stress through reasonable structural design; organic adhesion refers to a method that uses an adhesive as the connection material and combines metals and ceramics with different properties to form a mechanical whole through a certain bonding process; brazing is a welding process in which only the filler metal melts, wets the metal and ceramics, and forms a welded joint after solidification. However, the current connection techniques all have certain deficiencies. Among them, the stress at the mechanical connection is large, the ceramics are brittle, and the requirements for structural design are high; organic adhesion is generally manually operated, and it is difficult to achieve automation. Moreover, the above two connection methods both have limited application ranges, are sensitive to the operating environment temperature, and are not suitable for high-temperature and high-strength occasions, etc.; the physical and chemical properties of metal materials and ceramic materials are quite different, and there are differences in thermal expansion coefficients, etc. It is difficult for the filler metal to wet the ceramic surface, the processing temperature is high, and a protective gas or vacuum environment is required. On the one hand, the high-temperature and high-vacuum conditions greatly increase the production cost and are not conducive to large-scale industrial production. On the other hand, the high temperature will have a certain impact on the performance of the ceramic matrix. In order to address these problems, new solutions need to be developed. Summary of the Invention
[0004] An object of an embodiment of the present invention is to provide a carbon fiber composite barium titanate conductive ceramic material, aiming to solve the problems raised in the above background art.
[0005] The embodiments of the present invention are implemented as follows. A carbon fiber composite barium titanate conductive ceramic material, the chemical formula of the carbon fiber composite barium titanate conductive ceramic material is BaTiO3-xC, where 0 < x ≤ 0.1.
[0006] Preferably, x = 0.04.
[0007] Another object of the embodiments of the present invention is a preparation method of a carbon fiber composite barium titanate conductive ceramic material, including the following steps: Mixing and ball milling: Add anhydrous ethanol to ceramic powder, and add carbon fiber material, and continuously ball mill to make the powder uniformly mixed to form a slurry; Drying: Dry the slurry, remove ethanol, and grind to obtain uniformly mixed ceramic powder; Granulation and molding: Sieve the ceramic powder, add PVA solution to it and press it into shape, sieve it again after grinding and then press it into shape, and then statically press it into shape to form a green ceramic body; Debinding: Burry the green ceramic body in carbon fiber powder and keep it warm in an inert gas environment to obtain a ceramic blank; Sintering: High-temperature sinter the ceramic blank in an inert gas environment, and cool it to obtain the carbon fiber composite barium titanate conductive ceramic material.
[0008] Preferably, in the step of granulation and molding, the pressure for adding PVA solution and pressing it into shape is 180 - 220 MPa, the pressure for sieving it again after grinding and then pressing it into shape is 180 - 220 MPa, and the pressure for static pressing is 230 - 270 MPa.
[0009] Preferably, in the step of debinding, the temperature for keeping warm is 480 - 520 °C, and the time is 120 - 130 min.
[0010] Preferably, in the step of sintering, the temperature for high-temperature sintering is 1000 - 1100 °C, and the time is 2 - 2.5 h.
[0011] Another object of the embodiments of the present invention is the application of a carbon fiber composite barium titanate conductive ceramic material in the preparation of dielectric capacitors and piezoelectric devices.
[0012] A carbon fiber composite barium titanate conductive ceramic material provided by the embodiments of the present invention introduces carbon fiber as a conductive reinforcement into BaTiO3 (BT) ceramic, and prepares a carbon fiber composite barium titanate conductive ceramic by solid-phase sintering method. The carbon fiber enters the inside of the piezoelectric ceramic, and can maintain the complete carbon fiber morphology, acting as a current conductor inside the piezoelectric ceramic, effectively reducing the resistance of the piezoelectric ceramic. The resistance of a barium titanate piezoelectric ceramic sheet with a thickness of 1 mm and a diameter of 10 mm is generally 10 8In the order of Ω, after carbon fiber composite, the resistance of barium titanate can be effectively reduced to 30KΩ - 100KΩ. The composite material prepared in the embodiment of the present invention effectively reduces the resistivity of traditional barium titanate piezoelectric ceramics and can be used as an intermediate transition layer for the connection between barium titanate and metal, providing a new idea for the connection between barium titanate piezoelectric ceramics and metal. Description of the Drawings
[0013] Figure 1 SEM photograph of the material prepared in Comparative Example 1 of the present invention; Figure 2 XRD pattern of the material prepared in Comparative Example 1 of the present invention; Figure 3 SEM photograph of the carbon fiber used in the embodiment of the present invention; Figure 4 XRD pattern of the material prepared in Example 1 of the present invention; Figure 5 SEM photograph of the material prepared in Example 1 of the present invention; Figure 6 XRD pattern of the material prepared in Example 2 of the present invention; Figure 7 SEM photograph of the material prepared in Example 2 of the present invention; Figure 8 XRD pattern of the material prepared in Example 3 of the present invention; Figure 9 SEM photograph of the material prepared in Example 3 of the present invention; Figure 10 XRD pattern of the material prepared in Example 4 of the present invention; Figure 11 SEM photograph of the material prepared in Example 4 of the present invention; Figure 12 XRD pattern of the material prepared in Example 5 of the present invention; Figure 13 SEM photograph of the material prepared in Example 5 of the present invention; Figure 14 Bar chart of the resistance data of the materials prepared in Examples 1 - 5 and Comparative Example 1 of the present invention. Detailed Description of the Invention
[0014] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0015] A carbon fiber composite barium titanate conductive ceramic material, with the chemical formula BaTiO3-xC, where 0 < x ≤ 0.1. Its preparation method includes the following steps: (1) Mixing and ball milling: Add 1.5 times the mass of anhydrous ethanol to the ceramic powder, and then add the corresponding mass fraction of carbon fiber material. Continuously ball mill for 8 hours to make the powder mix evenly to form a slurry; (2) Drying: Place the slurry in an oven at 80 °C for constant-temperature drying to remove ethanol, and then grind it with a mortar to obtain a uniformly mixed ceramic powder; (3) Granulation and molding: Pass the powder through a 150-mesh sieve, then add a 3% mass concentration of PVA solution to it, mold it at 200 MPa, grind it and then pass it through a 150-mesh sieve to make the PVA mix evenly in the ceramic powder. Place the powder particles in a mold and press them into shape at a pressure of 200 MPa, and then isostatically press them at 250 MPa to form a green ceramic body; (4) Debinding: Bury the green ceramic body in carbon fiber powder, keep it at 500 °C for 120 minutes in a nitrogen atmosphere to discharge the PVA in the green ceramic body and obtain a ceramic blank; (5) Sintering: Sinter the ceramic blank in a nitrogen atmosphere at 1050 °C for 2 hours, and after cooling, obtain the carbon fiber composite barium titanate conductive ceramic material.
[0016] Grind and polish the prepared ceramic material to obtain a ceramic sheet about 0.9 mm thick, spray gold on both sides to obtain an electrode with a diameter of about 6 mm, and then the electrode can be measured.
[0017] The following combines specific embodiments to describe the specific implementation of the present invention in detail.
[0018] Example 1: A carbon fiber composite barium titanate conductive ceramic material, with the chemical formula BaTiO3-0.01C. Its preparation method includes the following steps: (1) Mixing and ball milling: Put 6 g of nano-barium titanate into a ball milling tank, add 0.06 g of carbon fiber powder, add 20 mL of anhydrous ethanol to submerge the raw materials and the carbon fiber powder, and continuously ball mill for 8 hours to make the powder mix evenly to form a slurry; (2) Filtration and drying: Filter out the slurry, place the slurry in an oven at 80 °C for constant-temperature drying to remove ethanol, and obtain a uniformly mixed ceramic powder; (3) Granulation and molding: Add 0.05 mL of a 3% mass concentration of PVA solution to it, grind it and then pass it through a 150-mesh sieve to make the PVA mix evenly in the ceramic powder. Place an appropriate amount of powder particles in a mold and press them into a ceramic disc with a size of about 10 mm in diameter and 1 mm thick at a pressure of 200 MPa, and then isostatically press them at 250 MPa to form a green ceramic body; (4)Debinding: The green ceramic body is buried in carbon fiber powder and placed in a corundum boat. Under a nitrogen atmosphere, it is kept at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank. (5)Sintering: Under a nitrogen atmosphere, the temperature is continuously raised, and the ceramic blank is sintered at 1050 °C for 2 hours, and a barium titanate-carbon fiber composite material is obtained after cooling. (6)Measurement: The obtained composite material is ground and polished to obtain a ceramic sheet about 0.9 mm thick, gold is sprayed on both sides to obtain electrodes with a diameter of 6 mm, and the electrodes are measured.
[0019] Example 2: A carbon fiber composite barium titanate conductive ceramic material with the chemical formula BaTiO3-0.02C, and its preparation method includes the following steps: (1)Mixing and ball milling: 6 g of nano-barium titanate is placed in a ball milling tank, 0.12 g of carbon fiber powder is added, and 20 mL of absolute ethanol is added to submerge the raw materials and the carbon fiber powder. Ball milling is continued for 8 hours to make the powder uniformly mixed to form a slurry. (2)Filtering and drying: The slurry is filtered out, placed in an oven at 80 °C for constant temperature drying to remove ethanol, and a uniformly mixed ceramic powder is obtained. (3)Granulation and molding: 0.05 mL of a PVA solution with a mass concentration of 3% is added thereto, ground and passed through a 150-mesh sieve to make the PVA uniformly mixed in the ceramic powder. An appropriate amount of powder particles are placed in a mold and pressed into a ceramic disc with a size of about 10 mm in diameter and 1 mm thick under a pressure of 200 MPa, and then isostatically pressed at 250 MPa to form a green ceramic body. (4)Debinding: The green ceramic body is buried in carbon fiber powder and placed in a corundum boat. Under a nitrogen atmosphere, it is kept at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank. (5)Sintering: Under a nitrogen atmosphere, the temperature is continuously raised, and the ceramic blank is sintered at 1050 °C for 2 hours, and a barium titanate-carbon fiber composite material is obtained after cooling. (6)Measurement: The obtained composite material is ground and polished to obtain a ceramic sheet about 0.9 mm thick, gold is sprayed on both sides to obtain electrodes with a diameter of 6 mm, and the electrodes are measured.
[0020] Example 3: A carbon fiber composite barium titanate conductive ceramic material with the chemical formula BaTiO3-0.04C, and its preparation method includes the following steps: (1)Mixing and ball milling: 6 g of nano-barium titanate is placed in a ball milling tank, 0.24 g of carbon fiber powder is added, and 20 mL of absolute ethanol is added to submerge the raw materials and the carbon fiber powder. Ball milling is continued for 8 hours to make the powder uniformly mixed to form a slurry. (2) Filtration and drying: Filter out the slurry, place the slurry in an oven at 80 °C for constant-temperature drying to remove ethanol, and obtain uniformly mixed ceramic powder; (3) Granulation and forming: Add 0.05 mL of PVA solution with a mass concentration of 3% to it, grind it and then pass it through a 150-mesh sieve to make the PVA uniformly mixed in the ceramic powder. Place an appropriate amount of powder particles in a mold and press them into a ceramic disc with a size of about 10 mm in diameter and 1 mm in thickness under a pressure of 200 MPa, and then perform isostatic pressing at 250 MPa to form a green ceramic body; (4) Debinding: Burry the green ceramic body in carbon fiber powder and put it into a corundum boat. Under a nitrogen atmosphere, keep it at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank; (5) Sintering: Continue to heat up under a nitrogen atmosphere and sinter the ceramic blank at 1050 °C for 2 hours, and obtain a barium titanate-carbon fiber composite material after cooling; (6) Measurement: Grind and polish the obtained composite material to obtain a ceramic sheet about 0.9 mm thick, sputter gold on both sides to obtain electrodes with a diameter of 6 mm, and measure the electrodes.
[0021] Example 4. A carbon fiber composite barium titanate conductive ceramic material with the chemical formula BaTiO3-0.06C. Its preparation method includes the following steps: (1) Mixing and ball milling: Put 6 g of nano barium titanate into a ball milling tank, add 0.36 g of carbon fiber powder, add 20 mL of anhydrous ethanol to submerge the raw materials and the carbon fiber powder, and continuously ball mill for 8 hours to make the powder uniformly mixed to form a slurry; (2) Filtration and drying: Filter out the slurry, place the slurry in an oven at 80 °C for constant-temperature drying to remove ethanol, and obtain uniformly mixed ceramic powder; (3) Granulation and forming: Add 0.05 mL of PVA solution with a mass concentration of 3% to it, grind it and then pass it through a 150-mesh sieve to make the PVA uniformly mixed in the ceramic powder. Place an appropriate amount of powder particles in a mold and press them into a ceramic disc with a size of about 10 mm in diameter and 1 mm in thickness under a pressure of 200 MPa, and then perform isostatic pressing at 250 MPa to form a green ceramic body; (4) Debinding: Burry the green ceramic body in carbon fiber powder and put it into a corundum boat. Under a nitrogen atmosphere, keep it at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank; (5) Sintering: Continue to heat up under a nitrogen atmosphere and sinter the ceramic blank at 1050 °C for 2 hours, and obtain a barium titanate-carbon fiber composite material after cooling; (6) Measurement: Grind and polish the obtained composite material to obtain a ceramic sheet about 0.9 mm thick, sputter gold on both sides to obtain electrodes with a diameter of 6 mm, and measure the electrodes.
[0022] Example 5. A carbon fiber composite barium titanate conductive ceramic material with the chemical formula BaTiO3-0.1C, and its preparation method includes the following steps: (1) Mixing and ball milling: Put 6 g of nano-barium titanate into a ball milling tank, add 0.6 g of carbon fiber powder, add 20 mL of absolute ethanol to submerge the raw materials and the carbon fiber powder, and continuously ball mill for 8 hours to make the powder mix evenly to form a slurry; (2) Filtration and drying: Filter out the slurry, place the slurry in an oven at 80 °C for constant temperature drying to remove ethanol, and obtain uniformly mixed ceramic powder; (3) Granulation and molding: Add 0.05 mL of a PVA solution with a mass concentration of 3% thereto, grind and pass through a 150-mesh sieve to make the PVA evenly mixed in the ceramic powder. Place an appropriate amount of powder particles in a mold and press them into a ceramic disc with a size of about 10 mm in diameter and 1 mm in thickness under a pressure of 200 MPa, and then perform isostatic pressing at 250 MPa to form a green ceramic body; (4) Debinding: Burry the green ceramic body in carbon fiber powder and put it into a corundum boat. Under a nitrogen atmosphere, keep it at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank; (5) Sintering: Continue to heat up under a nitrogen atmosphere and sinter the ceramic blank at 1050 °C for 2 hours, and obtain a barium titanate-carbon fiber composite material after cooling; (6) Measurement: Grind and polish the obtained composite material to obtain a ceramic sheet about 0.9 mm thick, sputter gold on both sides to obtain electrodes with a diameter of 6 mm, and measure the electrodes.
[0023] Comparative Example 1. A ceramic material with the chemical formula BaTiO3, and its preparation method includes the following steps: (1) Granulation and molding: Weigh 6 g of nano-barium titanate powder, add 0.05 mL of a PVA solution with a mass concentration of 3% thereto, grind and pass through a 150-mesh sieve to make the PVA evenly mixed in the ceramic powder. Place an appropriate amount of powder particles in a mold and press them into a ceramic disc with a size of about 10 mm in diameter and 1 mm in thickness under a pressure of 200 MPa, and then perform isostatic pressing at 250 MPa to form a green ceramic body; (2) Debinding: Burry the green ceramic body in carbon fiber powder and put it into a corundum boat. Under a nitrogen atmosphere, keep it at 500 °C for 120 minutes to discharge the PVA in the green ceramic body and obtain a ceramic blank; (3) Sintering: Continue to heat up under a nitrogen atmosphere and sinter the ceramic blank at 1050 °C for 2 hours, and obtain a barium titanate ceramic sheet material after cooling; (4) Measurement: Grind and polish the obtained ceramic sheet to obtain a ceramic sheet about 0.9 mm thick, sputter gold on both sides to obtain electrodes with a diameter of 6 mm, and measure the electrodes.
[0024] Performance test: The material prepared in Comparative Example 1 was tested, and the SEM photos are as follows Figure 1 As shown, according to Figure 1 It can be seen that in the case of no carbon fiber doping, the ceramic grains are in the form of nanoparticles; the XRD pattern obtained is as follows Figure 2 As shown, it is the BaTiO3 phase and there is no second phase; The carbon fiber used in the embodiment of the present invention was tested, and the SEM photos are as follows Figure 3 As shown, it can be seen that the carbon fibers are in the shape of rods and there are a small number of broken carbon fibers; The material prepared in Example 1 was tested, and the XRD pattern obtained is as follows Figure 4 As shown, there is no obvious difference compared with Comparative Example 1, showing the BaTiO3 phase and no obvious second phase; the SEM photos obtained are as follows Figure 5 As shown, obvious rod-shaped carbon fibers can be observed; The material prepared in Example 2 was tested, and the XRD pattern obtained is as follows Figure 6 As shown, there is no obvious difference compared with Comparative Example 1 and Example 1, showing the BaTiO3 phase and no obvious second phase; the SEM photos obtained are as follows Figure 7 As shown, obvious rod-shaped carbon fibers can be observed. Since the ceramic chip was broken to scan the ceramic chip, carbon fiber-shaped holes appear and the carbon fibers increase; The material prepared in Example 3 was tested, and the XRD pattern obtained is as follows Figure 8 As shown, there is no obvious difference compared with Comparative Example 1, Example 1, and Example 2, showing the BaTiO3 phase and no obvious second phase; the SEM photos obtained are as follows Figure 9 As shown, the carbon fibers continue to increase; The material prepared in Example 4 was tested, and the XRD pattern obtained is as follows Figure 10 As shown, there is no obvious difference compared with Comparative Example 1, Example 1, Example 2, and Example 3, showing the BaTiO3 phase and no obvious second phase; the SEM photos obtained are as follows Figure 11 As shown, the carbon fibers continue to increase; The material prepared in Example 5 was tested, and the XRD pattern obtained is as follows Figure 12 As shown, there is no obvious difference compared with Comparative Example 1, Example 1, Example 2, Example 3, and Example 4, showing the BaTiO3 phase and no obvious second phase; the SEM photos obtained are as follows Figure 13 As shown, the carbon fibers continue to increase; The resistances of the materials prepared in Examples 1-5 and Comparative Example 1 were measured, and the results are shown in Table 1: Table 1 ; As can be seen from Table 1, the resistance of the barium titanate ceramic sheet doped with carbon fiber is effectively reduced by an order of magnitude of 10 8 Ω, and it is found that when the doping ratio of carbon fiber is too high, the densification of the composite ceramic will be affected and the resistance will increase again; The bar chart of the resistance data is as Figure 14 shown, and it can be clearly seen that doping carbon fiber can reduce the resistance of barium titanate ceramics.
[0025] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A carbon fiber composite barium titanate conductive ceramic material, characterized in that: The chemical formula of the carbon fiber composite barium titanate conductive ceramic material is BaTiO3-xC, wherein 0<x≤0.
1.
2. The carbon fiber composite barium titanate conductive ceramic material according to claim 1, characterized in that: Said x=0.
04.
3. A method for preparing the carbon fiber composite barium titanate conductive ceramic material as claimed in claim 1 or 2, characterized in that: The following steps are involved: Mixing ball milling: add anhydrous ethanol to the ceramic powder and add carbon fiber material, and continue ball milling to mix the powders evenly to form a slurry; Drying: Dry the slurry, remove ethanol, and grind to obtain a uniformly mixed ceramic powder; Granulation: The ceramic powder is sieved, the PVA solution is added thereto and pressed, the powder is ground and sieved and then pressed, and then statically pressed to form a ceramic green body; Debinding: bury the ceramic green body in carbon fiber powder and keep it warm in an inert gas environment to obtain a ceramic green body; Sintering: sintering the ceramic blank at high temperature in an inert gas environment, and obtaining the carbon fiber composite barium titanate conductive ceramic material after cooling.
4. The method for preparing the carbon fiber composite barium titanate conductive ceramic material according to claim 3, characterized in that: In the step of granulation and molding, the pressure of adding PVA solution and pressing and molding is 180-220MPa, the pressure of grinding, sieving and pressing and molding is 180-220MPa, and the pressure of static pressure molding is 230-270MPa.
5. The method for preparing the carbon fiber composite barium titanate conductive ceramic material according to claim 3, characterized in that: In the step of debinding, the insulation temperature is 480-520° C. and the time is 120-130 minutes.
6. The method for preparing the carbon fiber composite barium titanate conductive ceramic material according to claim 3, characterized in that: In the sintering step, the high temperature sintering temperature is 1000-1100° C. and the time is 2-2.5 hours.
7. Use of the carbon fiber composite barium titanate conductive ceramic material as claimed in claim 1 or 2 in the preparation of dielectric capacitors and piezoelectric devices.